Secure and Privacy for Internet of Things data Modelling and Evaluation using Consortium-based Blockchain Consensus Methods - Chandra Priya J (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Over the last 20 years, IoT networks have undergone tremendous development. A major issue with this development is the massive amount of data generated by nodes, even though these devices often have limited memory, resources, and computing power. There, cloud computing comes into play by providing a place to store data. The centralization and robustness of a large network that uses cloud computing can make it susceptible to attacks. On top of that, devices might be vulnerable to attacks because access control settings aren't strong enough. Nonetheless, cloud computing offers a foundation for the implementation of such a security system. According to these standards, mobile and edge devices aren't part of a centralised, secure infrastructure. Because of this, many are beginning to doubt the reliability of cloud intermediaries as a whole, which can lead to security and privacy breaches. With an eye towards the Internet of Things (IoT) and cloud-native infrastructure, this study will examine the issue of blockchain architecture's consensus algorithms as they pertain to the Quorum and MultiChain variations. Keeping decentralisation, security, and public verifiability intact while scaling the core layer is a noteworthy problem. One way to speed up blockchains is to use consortium blockchain frameworks, which do away with smart contracts running in parallel. The difficulties of integrating blockchain technology into the Internet of Things (IoT) setting are better addressed.